2022
DOI: 10.3390/ijms23158272
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD4+ and CD8+ T Cell Biology by Short-Chain Fatty Acids and Its Relevance for Autoimmune Pathology

Abstract: The gut microbiota encodes a broad range of enzymes capable of synthetizing various metabolites, some of which are still uncharacterized. One well-known class of microbiota-derived metabolites are the short-chain fatty acids (SCFAs) such as acetate, propionate, butyrate and valerate. SCFAs have long been considered a mere waste product of bacterial metabolism. Novel results have challenged this long-held dogma, revealing a central role for microbe-derived SCFAs in gut microbiota-host interaction. SCFAs are bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…Epigenetic processes are a crucial aspect of 'autoimmunity' in many of its manifestations [26], including the following: (i) histone acetyltransferase (HAT) and histone deacetylase (HDAC), which regulate histone acetylation and alter histone spatial structure, thereby impacting on transcription. The gut microbiome influence on 'autoimmunity' includes variations in the levels of gut microbiome-derived butyrate, an HDAC inhibitor (HDACi), and regulator of the immune response in a number of 'autoimmune' conditions [27], including via enhanced Treg differentiation [28]; (ii) miRNAs, long non-coding RNAs (lncRNAs) and circular RNAs (CircRNA). miRNAs and the RNA-induced silencing complex (RISC) suppress mRNA transcription via binding to the mRNA 3 UTR region, including via complex formation.…”
Section: Classical Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic processes are a crucial aspect of 'autoimmunity' in many of its manifestations [26], including the following: (i) histone acetyltransferase (HAT) and histone deacetylase (HDAC), which regulate histone acetylation and alter histone spatial structure, thereby impacting on transcription. The gut microbiome influence on 'autoimmunity' includes variations in the levels of gut microbiome-derived butyrate, an HDAC inhibitor (HDACi), and regulator of the immune response in a number of 'autoimmune' conditions [27], including via enhanced Treg differentiation [28]; (ii) miRNAs, long non-coding RNAs (lncRNAs) and circular RNAs (CircRNA). miRNAs and the RNA-induced silencing complex (RISC) suppress mRNA transcription via binding to the mRNA 3 UTR region, including via complex formation.…”
Section: Classical Autoimmunitymentioning
confidence: 99%
“…The m 6 A methyltransferase METTL3 leads to mitochondrial dysfunction via mRNA modification of the 'master mitochondrial regulator', peroxisome proliferator-activated receptor gamma coactivator (PGC)-1α [35]. HDAC regulates a number of autoimmune disorders, with its inhibition by butyrate optimizing mitochondrial function [27]. Autoimmunity-associated suboptimal mitochondrial function can drive oxidative and nitrosative stress (O&NS) that induces miRNAs and lncRNAs, shown to be significant aspects of SLE pathophysiology [36], whilst a number of miRNAs increased in T1DM are strongly associated with suboptimal mitochondrial function [37].…”
Section: Mitochondrial Metabolism and 'Autoimmunity'mentioning
confidence: 99%
“…However, the level of SCFAs seems to be very important in inducing its function. Evidence shows that the anti-inflammatory effect of SCFAs is dose-dependent (117). Qi Hui et al (118) found that when butyrate concentration is 20 mmol, the levels of IL-6 and IL-1bwere significantly reduced, while the concentration was 2 mmol has no effect.…”
Section: Dietary and Gut Microbial Interactions In Cancer Immunotherapymentioning
confidence: 99%
“…Effector molecules such as CD25, IFN-γ, and TNF-α were then elevated in these treated cells, demonstrating enhanced cytotoxic activity and potential for pentanoate and C4 as supplements to cancer treatment for some malignancies (Figure 2D). (Schiweck et al, 2022).…”
Section: Molecular Impact Of Dysbiosis On Cd8 T Cell Signaling and Fu...mentioning
confidence: 99%